2012
DOI: 10.2320/matertrans.maw201202
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Mechanical Property on Nano-Co Particles Dispersed Al<sub>2</sub>O<sub>3</sub> via High-Temperature Oxidation

Abstract: Recovery of mechanical strength in ¡-Al 2 O 3 -based hybrid materials with 5 vol% dispersed nano-Co particles was carried out via a thermal oxidation process. Three Vickers indentations were conducted at 49 N for 10 s in air to introduce pre-cracks on the sample surface. The bending strengths of as-sintered and as-cracked samples were approximately 710 and 159 MPa, respectively. Bending strength value increased to 636 MPa when as-cracked specimens with introduced surface cracks were heat-treated at 1200°C for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…In order to overcome this disadvantage, there have been numerous studies attempting to provide ceramic matrix composites incorporating second‐phase dispersions such as platelets, fibers or whiskers, and particulates . In addition, dispersion of the secondary phases in the ceramic matrix composites contributes to its matrix self‐healing function when they are applied at high temperatures in the air …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to overcome this disadvantage, there have been numerous studies attempting to provide ceramic matrix composites incorporating second‐phase dispersions such as platelets, fibers or whiskers, and particulates . In addition, dispersion of the secondary phases in the ceramic matrix composites contributes to its matrix self‐healing function when they are applied at high temperatures in the air …”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10][11] In addition, dispersion of the secondary phases in the ceramic matrix composites contributes to its matrix self-healing function when they are applied at high temperatures in the air. [12][13][14][15][16][17][18][19][20][21] Self-healing function in ceramic-based composites such as SiC/mullite was first reported by Ando and his coworkers. 12 Oxidation of the SiC dispersoid in the matrix at high temperatures produced SiO 2 , the oxidation product that filled up and healed surface cracks.…”
Section: Introductionmentioning
confidence: 99%
“…32) Figure 9 shows the fraction of surface crack disappearance as a function of heat-treatment temperatures for 5Ni/mullite with the previously reported results on 5Ni/(10ZrO 2 + Al 2 O 3 ), 33) 5Ni/Al 2 O 3 , 34) and 5Co/Al 2 O 3 . 19) The Ni/mullite requires a lower heat-treatment temperature for surface crack-disappearance than the others nanocomposites based on Al 2 O 3 matrix. For example, a complete crack-disappearance for Ni/mullite is available with heat-treatment at 1100 C for 6 h in air.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…The self-healing function can be achieved variously at different heat-treatment conditions depending on the character-istics of the composites. In the most cases, the self-healing function could be obtained by heat-treatment in air at 1100-1300 C for SiC/mullite, 9,10) SiC/Al 2 O 3 , [11][12][13][14][15] 19) In some other cases, it can be obtained by heat-treatment in air at 800 C such as SiC/ZrO 2 . 20) Nevertheless, the bending strength of this composite was decreased from 700 MPa at room temperature to 180 MPa at 800 C. Nanko and his co-authors rstly reported the self-healing function for Ni/Al 2 O 3 nanocomposites, in which surface cracks completely disappeared by thermal oxidation process in air at 1200 C for 6 h. 21) The disappearance of surface cracks is caused by the formation of a surface layer composed of NiAl 2 O 4 -the oxidation product which is developed by diffusion of cations along grain boundaries of Al 2 O 3 matrix at high temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…The particular case of the Al 2 O 3 /Ni system has been extensively studied for a long time [3,7,8]. Al 2 O 3 /Co composites are considered an alternative to the Al 2 O 3 /Ni system, due to the superior properties of cobalt, like high melting temperature (1495°C) compared with the nickel systems and good biocompatibility [9][10][11]. The solution chemistry routes, in which metal nitrates are used as metal precursors for the production of ceramic/metal nanocomposites, could be advantageous to provide a fine-scale homogeneity [7,12].…”
Section: Introductionmentioning
confidence: 99%